Akuammiline alkaloid derivatives: divergent synthesis and effect on the proliferation of rheumatoid arthritis fibroblast-like synoviocytes - Bao, Xinye; Wei, Jian; Tao, Cheng; Bashir, Muhammad Adnan; Zhang, Hai-Jun; Bao, Bian; Chen, Jian; Zhai, Hongbin (Frontiers in Chemistry, 2023)
During the past decades, rheumatoid arthritis had become a serious problem, torturing millions of patients because of unclear pathogenesis and no ideal therapies. Natural products remain an important source of medicines to treat various major diseases such as rheumatoid arthritis (RA) given their excellent biocompatibility and structural diversity. Herein, we have developed a versatile synthetic method for constructing various skeletons of akuammiline alkaloid analogs based on our previous research on the total synthesis of the related indole alkaloids. We have also evaluated the effect of these analogs on the proliferation of RA fibroblast-like synoviocytes (FLSs) in vitro and analyzed the corresponding structure-activity relationship (SAR). Among these analogs, compounds 9 and 17c have demonstrated a promising inhibitory effect on the proliferation of RA-FLSs, with IC50 values of 3.22 ± 0.29 μM and 3.21 ± 0.31 μM, respectively. Our findings provide a solid foundation for future pharmacological studies on akuammiline alkaloid derivatives and inspiration for the development of anti-RA small molecule drugs derived from natural products.